Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Berpikir Kritis Kelas IV Pada Mata Pelajaran Matematika Sekolah Dasar - Nashiroh, Faridatun; Desstya, Anatri; Artik, Artik (LPPM Institut Pendidikan Nusantara Global, 2024)
The research aims to improve the critical thinking skills of fourth grade elementary school students in mathematics subjects by applying the Problem Based Learning (PBL) learning model. The method used in the research is classroom action research (PTK), with 2 cycles, each consisting of planning, implementation, observation and reflection stages. This research's data collection techniques include test techniques and non-test techniques. The test technique is a pretest-posttest in the form of multiple choices. Non-test techniques include observation, questionnaires and documentation. The research was conducted on 23 Class IV students at SD Muhammadiyah Plus Malangjiwan Colomadu. The data analysis technique was quantitative descriptive analysis. The results of this research show that the critical thinking abilities of fourth grade elementary school students have improved through the application of the PBL learning model in mathematics lessons. This can be seen from the pre-cycle to the second cycle with the initial average increasing from 51.1 to 77.9 (up 26.8), while the percentage increased from 54.89% to 84.56% (up 29.67%). The number of students who completed also increased from 3 to 23. Therefore, students' critical thinking skills increased significantly during the implementation of the PBL model from pre-cycle to cycle II. The results of the hypothesis test obtained a significance probability of 0.019 < 0.05 in cycle I and 0.004 < 0.05 in cycle II, so Ha was accepted, which means an increase in the critical thinking skills of fourth grade elementary school students was found by implementing the PBL model in mathematics lessons.